Dielectric properties, electric-field-induced polarization and strain behavior of Lead Zirconate Titanate-Strontium bismuth Niobate ceramics - Namsar O. (2017)
Â© 2016, Springer Science+Business Media New York. The dielectric properties and electric-field-induced polarization and strain behavior of (1-x)PZT-xSBN (x ranged from 0 to 1.0 weight fraction) ceramics prepared by a conventional mixed-oxide method were investigated. The dielectric properties indicated that the dielectric constant of PZT could be enhanced with small addition of SBN (xÂ =Â 0.1). From the polarization hysteresis loop measurements, it was found that the ferroelectric properties of nominal PZT-SBN ceramics changed strongly from the normal ferroelectric in PZT-rich ceramics to the paraelectric character in SBN-rich compositions. The strain hysteresis loops of nominal PZT-SBN under bipolar electric field loading suggested that the butterfly curve was observed in some compositions (0Â ≤Â xÂ ≤Â 0.3 and pure SBN ceramic). This research clearly showed the significance of SBN in controlling the electrical properties of nominal PZT-SBN ceramics.